New features of version 3 of the HYDRUS (2D/3D) computer software package - Šimunek, Jiří; Šejna, Miroslav; Van Genuchten, Martinus Th. [UNESP] (De Gruyter, 2018)
The capabilities of the HYDRUS-1D and HYDRUS (2D/3D) software packages continuously expanded during the last two decades. Various new capabilities were added recently to both software packages, mostly by developing new standard add-on modules such as HPx, C-Ride, UnsatChem, Wetland, Fumigant, DualPerm, and Slope Stability. The new modules may be used to simulate flow and transport processes in one- and two-dimensional transport domains and are fully supported by the HYDRUS graphical user interface (GUI). Several nonstandard add-on modules, such as Overland, Isotope, and Centrifuge, have also been developed, but are not fully supported by the HYDRUS GUI. The objective of this manuscript is to describe several additional features of the upcoming Version 3 of HYDRUS (2D/3D), which was unveiled at a recent (March 2017) HYDRUS conference and workshop in Prague. The new features include a flexible reservoir boundary condition, expanded root growth features, and new graphical capabilities of the GUI. Mathematical descriptions of the new features are provided, as well as two examples illustrating applications of the reservoir boundary condition.
Keywords: Graphical user interface; HYDRUS; Pumping well; Reservoir boundary condition; Root growth